Images Preaching – The Significance of Aesthetic Experiences with Artworks for the Art of Preaching - Gräb, Wilhelm (Stellenbosch Theological Journal, 2019)
Art confronts us with seeing our seeing as well as with the ambiguity of the meaning of what we see. This is the double transcendence of art whereby it acquires its theologicallynproductive function. In this article I want to show that images of art can preach andn how they do so, using as illustrations stained-glass windows by Johannes Schreiter in the Jakobi-Kirche in Göttingen, and a work of art that was shown at dOCUMENTA 13 (2012) in Kassel. Works of art can irritate our eyes. There is also the beauty of humour and folly that works of art can bring to preaching. If you have a sense of humour, you can see many things – especially those that are obviously distressing and oppressive – quite differently, and even give the negative a positive interpretation. Artworks can express such humour or motivate us to perceive it. I demonstrate at the end of this article how a contemporary painting conveying a disturbing picture of the crucified Christ can inspire preaching.